The characteristics of gelatin from fish waste: A review - Asmawati, Asmawati; Fahrizal, Fahrizal; Arpi, Normalina; Amanatillah, Dara; Husna, Fazilatul (Aceh Journal of Animal Science, 2023)
Gelatin is a commonly used ingredient in the food, pharmaceutical, and cosmetic industries. It is obtained through the hydrolysis process of collagen, the main protein found in animal connective tissues.Fish waste such as skin and bone are a promising source for gelatin, however the characteristics of gelatin can vary depending on its source.The purpose of this review is to compare the characteristics of gelatin from fish skin and bones, such as yield, gel strength, and viscosity. The research findings indicate significant differences in the characteristics of gelatin from different types of fish skin and bones. In this study, it was found that gelatin with the best characteristics was derived from the skin of mackerel fish, with a yield of 5.90%, viscosity of 7 cP, and gel strength of 328.57 g bloom. Meanwhile, gelatin from the bones of tilapia fish had a yield of 8.10%, viscosity of 5.85 cP, and gel strength of 376.21 g bloom.It was concluded that gelatin from various types of fish skin and bones had different characteristics, so the specific purpose of using the obtained gelatin had to be considered.